Requirements of job satisfaction for female leaders in kindergarten in West of Riyadh - Alotaibi, Asma Dowihi; Alfahad, Entesar Fahad; Almoklfl, Ruoof Eid; Madkali, Zahra Ali; Alaskar, Sarah Sami; Alaskar, Sarah Fahad; Al-Azzam, Noura (Journal of Educational and Psychological Sciences, 2020)
The main objective of this study was to identify the requirements of job satisfaction for kindergarten leaders in western Riyadh. The researchers used the descriptive approach (survey). All members of the present study population were selected. The sample consisted of 33 kindergarten leaders who work in western Riyadh. To meet the study’s objectives, the questionnaire was used as a tool to collect information that included (25) phrases to cover the four elements. The findings of this study revealed that kindergarten leaders in western Riyadh city experience overall an average score with 2.27 from 3, of job satisfaction requirements. At the element level; The relations with female employees achieved a high degree with an average of 2.44, the self-esteem achieved a high degree with an average of 2.38, the job assignments and duties achieved a medium degree with an average 2.28, and the incentives achieved a degree Medium with an average 1.98.
Keywords: requirements; job satisfaction; female leaders; women leaders; kindergarten; West of Riyadh